Inequalities in access to biological treatments for psoriasis: results from the Italian Psocare registry. (1st May 2017) - Naldi, L.; Cazzaniga, S.; Di Mercurio, M.; Grossi, E.; Addis, A.
Summary: Background: Limited evidence is available on the impact of socioeconomic factors on drug prescriptions for psoriasis. Objectives: To investigate factors influencing prescription of conventional vs. biological treatment for patients with psoriasis, based on the Italian Psocare registry, with a special focus on socioeconomic factors. Methods: This was a cross‐sectional study evaluating the baseline data of patients included in the Psocare registry. All of the consecutive adult patients with a diagnosis of chronic plaque psoriasis or psoriatic arthritis who were prescribed a systemic treatment for psoriasis at participating centres were included in this study. Univariate and multivariate analyses of the baseline factors associated with a biologics prescription were performed. Results: From September 2005 to September 2009, 12 838 patients were identified. A multivariate analysis revealed that, among other factors, completing a level of education higher than lower secondary school and being employed as a manager or a professional were independent factors associated with a biologics prescription at entry in the registry. Additional analyses on the association between these two variables and a severe psoriasis condition [Psoriasis Area Severity Index (PASI) score > 20] revealed a significantly increasing trend of severe disease towards lower educational attainment, while unemployed patients were more likely to have a more severe condition compared with the other categories of workers. Conclusions: We documented inequalities of drug prescriptions for psoriasis in Italy, with a trend towards a higher frequency of prescription for more expensive biologics in higher socioeconomic sectors of the population.